Hydrogen Bonding versus Halogen Bonding: Spectroscopic Investigation of Gas‐Phase Complexes Involving Bromide and Chloromethanes. Issue 7 (3rd January 2023) - Robinson, Hayden T.; Haakansson, Christian T.; Corkish, Timothy R.; Watson, Peter D.; McKinley, Allan J.; Wild, Duncan A.
Abstract: Hydrogen bonding and halogen bonding are important non‐covalent interactions that are known to occur in large molecular systems, such as in proteins and crystal structures. Although these interactions are important on a large scale, studying hydrogen and halogen bonding in small, gas‐phase chemical species allows for the binding strengths to be determined and compared at a fundamental level. In this study, anion photoelectron spectra are presented for the gas‐phase complexes involving bromide and the four chloromethanes, CH3 Cl, CH2 Cl2, CHCl3, and CCl4 . The stabilisation energy and electron binding energy associated with each complex are determined experimentally, and the spectra are rationalised by high‐level CCSD(T) calculations to determine the non‐covalent interactions binding the complexes. These calculations involve nucleophilic bromide and electrophilic bromine interactions with chloromethanes, where the binding motifs, dissociation energies and vertical detachment energies are compared in terms of hydrogen bonding and halogen bonding. Abstract : Hydrogen bonding and halogen bonding have been investigated via anion photoelectron spectroscopy. Gas‐phase complexes involving bromide and chloromethanes were observed, and their associated electron binding energies were measured. High‐level CCSD(T) calculations were used to determine the non‐covalent interactions binding the complexes.